Decrease of Sensorineural Hearing Frequency and Cochlear Hair Cell Function in Malignant Head and Neck Tumor Post Cisplatin Chemotherapy Series II - Irawati1. Bakti Surarso1.Haris M. Ekorini1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Malignancy in head and neck is mostly squamous cell carcinoma which are relatively radiosensitive. Giving chemotherapy combination of cisplatin-5 fluorouracil most frequently used in Lotus inpatients unit of Dr. Soetomo General Hospital Surabaya. Purpose : This study aimed to prove the decrease of sensorineural hearing frequency and cochlear hair cells function in malignant head and neck tumors patients post- cisplatin chemotherapy series II. Method: The samples were malignant head and neck tumor patients that would receive cisplatin chemotherapy. The inclusion criteria wereaged 18 to 65 years, malignant head and neck tumors planning to get cisplatin chemotherapy, intact tympanic membrane, ANM checks within normal limits. Tympanogram type A, DPOAE examination with pass results. Results: Pre-and post-cisplatinchemotherapy series I did not obtain any changes, those were pass on all frequencies. Mc Neymar test on DPOAE post-cisplatin chemotherapy I obtained p = 0.250 in 6 kHz frequency (p>0.05). DPOAE post-cisplatin II in 6 kHz frequency showed no significant difference (p>0.05) Conclusion: There was no decrease of outer cochlear hair cells function in malignant head and neck tumors patients who received cisplatin chemotherapy series II.